Clinicopathological studies of Pasteurella multocida B:2 experimental infection in rabbits - PATEL, S J; JOSHI, D V; RAVAL, S H; PATEL, B J; PATEL, J G; CHAUHAN, H C; CHANDEL, B S; PATEL, B K; SHAH, N M (The Indian Journal of Animal Sciences, 2016)
The present study was carried out to study pathology and virulence of Pasteurella multocida B:2 isolated from natural outbreak of Pasteurella infection in rabbits. Healthy Pasteurella multocida B:2 free rabbits (12) were divided in control and challenged group. The challenged group rabbits were inoculated intra-nasally by spraying of 0.5 ml of inoculum in each nares, containing 1 × 105 CFU of Pasteurella multocida B:2 in BHI. The control group of rabbits was inoculated with 0.5 ml uncultured BHI broth in each nares in the same manner. Live animals were observed for atleast 14 days. The main clinical signs observed in infected rabbits comprised of conjunctivitis, nasal discharge, pyrexia, sneezing, dyspnoea and abdominal breathing. The pathomorphological changes in lungs comprised of acute fibrinous and/or fibrino suppurative bronchopneumonia/pleuropneumonia. Trachea showed acute inflammatory changes with multifocal erosion/ulcer and necrosis. Nasal cavity showed acute inflammation with accumulation of cellular debris in nasal meatus. Three infected rabbits showed meningitis characterized by congestion, infiltration of heterophils and minimal oedema. Pasteurella multocida B:2 was successfully detected in blood and tissues of infected rabbits by PCR. The organisms were also demonstrated in blood/impression smear from different organs.